Cerebral glucose metabolism and cognition in newly diagnosed Parkinson's disease: ICICLE-PD study. Issue 4 (6th October 2016) - Firbank, M J; Yarnall, A J; Lawson, R A; Duncan, G W; Khoo, T K; Petrides, G S; O'Brien, J T; Barker, R A; Maxwell, R J; Brooks, D J; Burn, D J
Abstract : Objective: To assess reductions of cerebral glucose metabolism in Parkinson's disease (PD) with 18F-fluorodeoxyglucose (FDG) positron emission tomography (PET), and their associations with cognitive decline. Methods: FDG-PET was performed on a cohort of 79 patients with newly diagnosed PD (mean disease duration 8 months) and 20 unrelated controls. PD participants were scanned while on their usual dopaminergic medication. Cognitive testing was performed at baseline, and after 18 months using the Cognitive Drug Research (CDR) and Cambridge Neuropsychological Test Automated Battery (CANTAB) computerised batteries, the Mini-Mental State Examination (MMSE), and the Montreal Cognitive Assessment (MoCA). We used statistical parametric mapping (SPM V.12) software to compare groups and investigate voxelwise correlations between FDG metabolism and cognitive score at baseline. Linear regression was used to evaluate how levels of cortical FDG metabolism were predictive of subsequent cognitive decline rated with the MMSE and MoCA. Results: PD participants showed reduced glucose metabolism in the occipital and inferior parietal lobes relative to controls. Low performance on memory-based tasks was associated with reduced FDG metabolism in posterior parietal and temporal regions, while attentional performance was associated with more frontal deficits. Baseline parietal to cerebellum FDG metabolism ratios predicted MMSE (β=0.38, p=0.001) and MoCA (β=0.3, p=0.002) at 18 months controlling for baseline score. Conclusions: Reductions in cortical FDG metabolism were present in newly diagnosed PD, and correlated with performance on neuropsychological tests. A reduced baseline parietal metabolism is associated with risk of cognitive decline and may represent a potential biomarker for this state and the development of PD dementia.